Analytical and Gravimetrical Studies of the Corrosion Inhibitory Behavior of Carnosine - Fadhil, Dhuha H (Al-Nahrain Journal of Science, 2018)
The corrosion inhibition characteristics of Carnosine (2-(3-aminopropanamido)-3-(1H-imidazol-5-yl) propanoic acid) in corrosive solution for mild steel have been investigated at 30ºC through gravimetrical technique namely Weight loss method. The morphology study of mild steel with and without Carnosine to impedance the corrosion for mild steel in 1.0 M hydrochloric acid has been figured, utilizing with scanning electron microscopy (SEM). The results show that the investigated Carnosine might be an excellent corrosion inhibitor with enhanced inhibition efficiency of 91%. The inhibition effectiveness of the Carnosine raising with increase of Carnosine concentrations, and decreases with increasing of temperature corrosion solution.[DOI: 10.22401/JNUS.21.3.10]